Chemical Composition of Syzygium cumini (L.) Skeels Leaf Essential Oil with Respect to its Uses from North East Region of India. Issue 3 (3rd May 2020) - Sarma, Neelav; Begum, Twahira; Pandey, Sudin Kumar; Gogoi, Roktim; Munda, Sunita; Lal, Mohan
Abstract: Syzygium cumini (L.) Skeels (Jambolan) is a widespread summer fruit plant, well-known for various therapeutic uses such as anti-diabetic, antimicrobial, antioxidant properties. The fruit helps to convert starch into energy which helps in regulating blood sugar levels and possesses a low glycemic index. The present study is aimed to estimate the chemical composition of the essential oil of leaves of Syzygium cumini through GC/MS. The essential oil was extracted by hydrodistillation using a Clevenger apparatus which was further analyzed through GC/MS. The GC/MS analysis identified twenty-five components with a total area percentage of 95.66 %. The major identified components were τ-cadinol (21.44 %) and tau-muurolol (12.01 %). The compounds of intermediate concentration were globulol (7.98 %), caryophyllene (6.69 %), δ-cadinene (6.56%) and α-pinene (6.32 %). While β-eudesmol (4.42 %), β-pinene (4.32 %), γ-cadinene (3.87 %), camphene (2.98 %), α-terpinenol (2.72 %), camphor (2.23 %), humulene 6, 7-epoxide (2.17 %), cubeban-11-ol (1.98 %), α-muurolene (1.81 %), epicubenol (1.43 %), α-copaene (1.26 %), viridiflorene (1.02 %), β-guanine (0.65 %), β-bourbonene (0.23 %), terpinen-4-ol (0.13 %), endo-borneol (0.12 %), levoverbenone (0.12 %) and isobornyl acetate (0.12 %) were the compounds present in minor concentrations. Among the identified compounds there were monoterpene hydrocarbons (13.62 %), bicyclic-monoterpenoid (0.36 %), terpenoid ketones (2.23 %), monocyclic monoterpenoid alkene alcohol (2.85 %), non-oxygenated sesquiterpenes (25.17 %) and oxygenated sesquiterpenes (51.43 %). The present investigation also discusses the applications of various components found in S. cumini leaf essential oil and a comparative view on the essential oil composition of the leaves of the plant was reported earlier.